Enhancing Security Protection using Elliptic Curve Encryption and Digital Signature in Vehicular Ad-Hoc Network - Selvakumar, K.; Naveen Kumar, S. (International Journal of Engineering and Technology, 2018)
The Vehicular Ad-Hoc Network (VANET) is a liberality vehicle acts as remote switch or node in a cellular system. The VANET is much reasonable because of the single framework attributes agree to the system to be unbolted to metro. In this paper, we propose a Secure Hash Algorithm (SHA-1) to make an interesting key to every message. Likewise, prescribe capable and reasonable alias convention with prohibitive disconnection propagation. We set forward prime pseudonyms reasonably make a long time cycle that are worn to interact with semi-confided in experts and alternate pseudonyms with a minor lifetime which are utilized to talk with different nodes. Likewise, suggestion in the digital signature utilized in VANET is the basic, ECEDS (Elliptic Curve Encryption and Digital Signature). ECEDS enrich with system security by using a digital signature for the messages actually communicated with the system.Â Â